High-resolution estimation of air pollutant emissions from vegetation burning in China (2000–2018) - Yang, Wei; Jiang, Xiaoli (Frontiers in Environmental Science, 2022)
Natural vegetation burning in China contributes significantly to atmospheric pollution and climate change. However, most recent studies focused mainly on forest fires, ignoring grassland fires. Besides, there was a generally high uncertainty in the estimated fire emission because of missing small fire data and limited local vegetation data. This study employed high-resolution burned area data (GABAM, global annual burned area map) and land cover data to develop a high-resolution emission inventory of natural vegetation burning in China in 2000, 2005, 2010, 2015, and 2018. The cumulative pollutant emissions from the temporal and spatial variation analyses of the burned area and emissions reached 1.01 × 105 Gg. Specifically, the total emissions of CO, CH4, NOx, non-methane volatile organic carbon, SO2, NH3, PM2.5, PM10, organic carbon, black carbon, and CO2 were 4.39 × 103, 149, 152, 497, 42, 78, 634, 792, 370, 25, and 9.42 × 104 Gg, respectively. The South, Southwest, East, and Northeast of China contributed the most emissions. Shrubland contributed the most emissions for different vegetation types, followed by forest and grassland. Consequently, this study provides scientific evidence to support understanding the influence of fire on the local environment and policy on China's air pollution control.